Understanding Accessibility in MOOCs: Findings and Recommendations for Future Designs - Francisco Iniesto; Covadonga Rodrigo (Journal of Interactive Media in Education)
Ensuring accessibility in Massive Open Online Courses (MOOCs) is essential to enable learners with accessiblity needs to fully engage in and derive benefits from online learning experiences. Prioritising accessibility in MOOCs not only adheres to principles of social inclusion but also amplifies the overall effectiveness of online education, creating a learning environment where all participants can thrive and actively contribute. However, there is currently a limited understanding of accessibility in MOOCs. To bridge this gap, this paper presents a systematic literature review of 20 papers, examining the current state of the art, and offers key recommendations for implementing accessibility. The findings highlight the importance of involving all stakeholders, including MOOC providers, course developers, and learners, in including accessibility in MOOCs by using co-creation and participatory design methodologies. This systematic literature review contributes to building an evidence base that can guide the development and integration of accessibility in online educational contexts by organising pertinent literature into cohesive themes that offer insights for future research.